(untitled) (Journal of Engineering, 2014)
Energy use is second to staffing in building operating costs. Sustainable technology in the energy sector is based on utilizing renewable sources of energy such as solar, wind, glazing systems, insulation. Other areas of focus include heating, ventilation and air conditioning; novel materials and construction methods; improved sensors and monitoring systems; and advanced simulation tools that can help building designers make more energy efficient choices. The objective of this research is studying the effect of insulations on energy consumption of buildings in Iraq and identifying the amount of energy savings from application the insulations in buildings. HAP (Hourly Analysis Program) is used to calculate the thermal loads and the amount of energy needed. It is concluded that the use of the thermal insulation in the roof, walls, floors, and double glazing system for windows in building effectively reduces the energy required for air conditioning.